Gender perspectives in a teacher education distance programme - Bailey, Barbara (Women's Studies Centre, 1993)
An examination of registration data for programmes offered via the distance education mode at The University of the West Indies (UWI) showed that, as with the face-to-face programme, a higher proportion of women than men were using this route as a means of obtaining accreditation. The article identifies factors that could have a differential impact on female and male participants in the teacher education programme offered via the distance teaching network (UWIDEC), and presents the findings of a survey
Keywords: Gender analysis